Tinjauan Hukum dan Kebijakan Siyasah Maliyah terhadap Pajak Penghasilan bagi Tiktokers di Indonesia - Aminullah, Irma; Rakhmah, Kamiliya Noer (Civil Officium: Journal of Empirical Studies on Social Science, 2024)
The purpose of this study is to find out the income tax system in Indonesia and whether the collection of taxes for Tiktokers is in accordance with the concept of the benefit of the people in Siyasah Maliyah. The research method used is normative juridical by taking a direct approach to the law and a conceptual approach. The results of this study are that current arrangements regarding income tax for Tiktokers have not been explicitly regulated in existing laws. There is a different opinion regarding the activities of Tiktokers workers among the Directorate of Taxes which ends in legal uncertainty for the existence of the withdrawal of Tiktokers' income tax in Indonesia. However, the Tax Regulation Directorate Section I, the Tax Regulation Directorate II, and the PKP Directorate agree that Tiktokers are finally classified as KLU 90002. This opens the opportunity for the Tiktokers' income tax obligations to be guaranteed to be paid, calculated, and reported.